STRATEGI INTEGRATED MARKETING COMMUNICATION (IMC) USAHA KECIL GALLERAJ BANDUNG DALAM MENINGKATKAN DAYA SAING USAHA KECIL DI ERA DIGITAL - Yanti Susilawati Tresnawati; Iskandar, Trias Pyrenia (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
The COVID-19 pandemic has created quite a crucial problem for small business actors. These problems are in the form of hampered distribution of materials including, difficulty in finding raw materials, difficulty in the capital, hampered production, and declining sales. One of the Small Business actors affected by the sale is the Rajut Galleraj business. Galleraj focuses on the existence of product sales to be able to compete amid dynamic conditions in the new average era. To be able to maintain the market with a different strategy. However, along with the intense competition for buying and selling online, the researcher wants to analyze how the Integrated Marketing Communication strategy at MSME Galleraj. The specific objectives of this study are to 1. Map and describe the Integrated Marketing Communication Strategy at Galleraj in New Normal Competition 2. To analyze the development of the Integrated Marketing Communication (IMC) Strategy in online media. Keywords: Small Business, Survival, Online Marketing.